2010
DOI: 10.1002/0471142700.nc1702s40
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Formation of G‐Quadruplex Structures

Abstract: There are many structures that can be adopted by nucleic acids other than the Watson-Crick duplex. In particular, a noncanonical four-stranded topology, called a G-quadruplex, is of great interest because of its roles in key biological processes such as the maintenance of telomeres and regulation of gene transcription. This review describes the condition for forming the G-quadruplex structure, G-quadruplex-forming sequences, and methods for studying the structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 127 publications
(131 reference statements)
0
32
0
Order By: Relevance
“…In addition to sequence modifications, another common approach to reduce polymorphism is by changing the solution conditions. The addition of biological molecules 59 (e.g. sugar, proteins), presence of co-solvents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to sequence modifications, another common approach to reduce polymorphism is by changing the solution conditions. The addition of biological molecules 59 (e.g. sugar, proteins), presence of co-solvents (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[26] Thea ddition of the complementary sequence (nt 184-208) yielded aT mo f7 3 8 8 Cf or the duplex. [26] Combined with our RTS-HBLMPCR result here (Figure 5A), it is likely that the G4s and P1 helix coexists in full length hTERC,with G4s being more stable than the P1 helix (weak GU pairs and internal loop) under physiological conditions which have high [K + ], about 150 mm.W ec annot rule out the possibility that both structures could form simultaneously with aq uadruplex comprising aCbulge (nt [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. [24] Recent protein binding and RNAmutational studies have suggested that the RNAG4-specific helicase DHX36 is involved in the binding and unwinding of aputative RNAG4 located near the 5 end of hTERC, [27] and that the G4 may facilitate the accumulation of mature hTERC needed for telomere maintenance.…”
Section: Methodsmentioning
confidence: 99%
“…[6] G4 structures exhibit characteristic features in circular dichroism, UV-thermal melting analysis,f luorescence,a nd NMR spectroscopy. [7] Thes ynthetic or in vitro transcribed (IVT) RNAc an be subjected to in-line probing to detect the presence of RNA G4s.…”
mentioning
confidence: 99%
“…3.6 G-tetraduplex and genetic instability G-quadruplexes are higher-order DNA or RNA structures formed from G-rich DNA or RNA sequences that are built around tetrads of hydrogen-bonded guanine bases (Lipps & Rhodes, 2009;Sannohe & Sugiyama, 2010). Despite the wide prevalence of genomic sequences that have G-rich property and that can potentially fold into tetraplex / quadruplexes structures, a direct demonstration of their existence in vivo proved to be a difficult undertaking.…”
Section: H-dna and H-dna Induced Dsbs And Genetic Instabilitymentioning
confidence: 99%